Minimal Detectable Change in Dual-Task Cost for Older Adults With and Without Cognitive Impairment. Issue 4 (October 2019) - Venema, Dawn M.; Hansen, Haley; High, Robin; Goetsch, Troy; Siu, Ka-Chun
Abstract : Background and Purpose: Dual-task (DT) training has become a common intervention for older adults with balance and mobility limitations. Minimal detectable change (MDC) of an outcome measure is used to distinguish true change from measurement error. Few studies reporting on reliability of DT outcomes have reported MDCs. In addition, there has been limited methodological DT research on persons with cognitive impairment (CI), who have relatively more difficulty with DTs than persons without CI. The purpose of this study was to describe test-retest reliability and MDC for dual-task cost (DTC) in older adults with and without CI and for DTs of varying difficulty. Methods: Fifty participants 65 years and older attended 2 test sessions within 7 to 19 days. Participants were in a high cognitive group (n = 27) with a Montreal Cognitive Assessment (MoCA) score of 26 or more, or a low cognitive group (n = 23) with a MoCA score of less than 26. During both sessions, we used a pressure-sensing walkway to collect gait data from participants. We calculated motor DTC (the percent decline in motor performance under DT relative to single-task conditions) for 4 DTs: the Timed Up and Go (TUG) while counting forward by ones (TUG1) and counting backward by threes (TUG3); and self-selected walking speed (SSWS) with the same secondary tasks (SSWS1 and SSWS3). Intraclass correlation coefficients (ICCs) and MDCs were calculated for DTC for the time to complete the TUG and spatiotemporal gait variables during SSWS. A 3-way analysis of variance was used to compare differences in mean DTC between groups, tasks, and sessions. Results and Discussion: ICCs varied across groups and tasks, ranging from 0.02 to 0.76. MDCs were larger for individuals with low cognition and for DTs involving counting backward by threes. For example, the largest MDC was 503.1% for stride width during SSWS3 for individuals with low cognition, and the smallest MDC was 5.6% for cadence during SSWS1 for individuals with high cognition. Individuals with low cognition demonstrated greater DTC than individuals with high cognition. SSWS3 and TUG3 resulted in greater DTC than SSWS1 and TUG1. There were no differences in DTC between sessions for any variable. Conclusions: Our study provides MDCs for DTC that physical therapists may use to assess change in older adults who engage in DT training. Persons with low cognition who are receiving DT training must exhibit greater change in DTC before one can be confident the change is real. Also, greater change must be observed for more challenging DTs. Thus, cognitive level and task difficulty should be considered when measuring change with DT training. Abstract : Supplemental Digital Content is Available in the Text.